Fostering Sustainability through the Integration of Renewable Energy in an Agricultural Hydroponic Greenhouse - Lachheb, Aymen; Marouani, Rym; Mahamat, Chabakata; Skouri, Safa; Bouadila, Salwa (Engineering, Technology & Applied Science Research, 2024)
This research explores the feasibility of integrating renewable energy sources, such as solar and wind, to power a hydroponic greenhouse. In this way, the latter’s energy autonomy is ensured. The study begins by evaluating the annual electricity consumption of the examined system. A renewable energy system capable of meeting its energy requirements throughout the year is also designed. The main objective is to assess the efficiency of two types of renewable energy sources, namely photovoltaic panels and wind turbines, and to improve their integration within the agricultural chamber by implementing a model simulation. Two scenarios were examined: the first one represents a photovoltaic power plant with storage, connected to the grid, while the second scenario presents a wind power plant connected to the grid. This numerical analysis is supplemented by a one-year experimental study of a photovoltaic installation connected to the network with storage, which in turn is connected to the experimental device. To handle energy within the renewable energy greenhouse, an energy management system was developed based on a fuzzy logic controller. This system aims to maintain energy balance and ensure continuous power supply. The energy management system optimizes energy flow to minimize consumption, reduce grid dependence, and improve overall system efficiency, resulting in cost savings and certain environmental benefits.